effect of doping with nitrogen on the optical constant of the sic films prepared by TEA-Co2 Laser - Baghdad Science Journal (مجلة بغداد للعلوم)
In this research prepare membranes pure silicon carbide (SiC) as well as gas Alloy (ammonia) and using a laser was leaked membrane of glass flooring. To Drasesh optical properties of membranes prepared depending on the technique (Swanepoel) and Adhrt results obtained in general increased permeability pure silicon membranes